Quantifying Cutting and Wearing Behaviors of TiN- and CrN-Coated AISI 1070 Steel - Cakan, Ahmet; Ozkaner, Vedat; Yildirim, Mustafa M. (Mdpi, 2008)
Hard coatings such as titanium nitride (TiN) and chromium nitride (CrN) are widely used in cutting and forming tools against wear and corrosion. In the present study, hard coating films were deposited onto AISI 1070 steels by a cathodic arc evaporation plating ( CAVP) technique. These samples were subjected to wear in a conventional lathe for investigating the tribological behaviour of coating structure, and prenitrided subsurface composition was characterized using scanning electron microscopy (SEM), line scan analyses and X-ray diffraction ( XRD). The wear properties of TiN- and CrN-coated samples were determined using an on-line monitoring system. The results show that TiN- coated samples demonstrate higher wear resistance than CrN-coated samples.
Keywords: TiN-coating; CrN-coating; cutting performance; tool wear on-line monitoring; cutting force